Function of Tumor Suppressors in Resistance to Antiandrogen Therapy and Luminal Epithelial Plasticity of Aggressive Variant Neuroendocrine Prostate Cancers - Soundararajan, Rama; Aparicio, Ana M.; Logothetis, Christopher J.; Mani, Sendurai A.; Maity, Sankar N. (Frontiers in Oncology, 2018)
Combined loss of tumor suppressors (TSPs) PTEN, TP53, and RB1 is highly associated with small cell carcinoma of prostate phenotype. Recent genomic studies of human tumors as well as analyses in mouse genetic models have revealed a unique role for these TSPs in dictating epithelial lineage plasticity – a phenomenon that plays a critical role in the development of aggressive variant prostate cancer and associated androgen therapy resistance. Here, we summarize recently published key observations on this topic, and hypothesize a possible mechanism by which concurrent loss of TSPs could potentially regulate the prostate cancer disease phenotype.